Experimental and numerical analysis of mechanical behaviors of long-term atmospheric corroded Q235 steel. (May 2022) - Guo, Qi; Zhao, Yun; Xing, Ying; Jiao, Jinfeng; Fu, Benzhao; Wang, Yuqing
Abstract: In the present study, microscopic and tensile tests are carried out on specimens corroded in the atmosphere for 33 years to quantitatively analyze the degradation of corroded Q235 steel. Results show that the mass loss ratio of steel members can reach up to 0.1309. Also, it was found that the pit depth and aspect ratio obey the Gaussian distribution with their mean values of 0.396 and 0.219, respectively. Corrosion pits significantly reduce the yield strength, ultimate strength, elastic modulus, and ductility, among which the elongation is reduced by up to 24.51%. In addition, a new pitting model, in which the pitting fusion is included, is presented. It will be shown that this model can more accurately count and measure pits. Based on this model, a numerical parameter analysis of steel members with random pits is conducted using the ABAQUS software and NumPy package in Python software. New nonlinear relationships between mass loss ratio and strengths are proposed to better explain the effects of variation of stress concentration caused by corrosion pits evolution. Also, it will be shown that this model can be used to predict the strength degradation more accurately.